Errors of Arabic Writing - Zulfa Nur Ikhwan; Ahmad Mufarih Hasan Fadly (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2019)
This research is an error analysis study that aims to describe the primary forms of error in writing Arabic following the rules of the 'imla' and the factors that influence it on the guidance participants of the Amtsilati Darussalam Council of the Islamic Boarding School in Blokagung Banyuwangi. This research is field research, where the approach uses qualitative methods descriptive analytics for data processing. In this study the authors used several methods namely methods of data collection and data analysis which use several ways including observations, tests, interviews, and documentation so that it can describe learning activities, forms of fundamental errors in writing Arabic such as writing errors hamzah qatha', reduction harf, addition harf, writing harf toothed, writing harf continued and separate, replacement harf and the factors that influence it on the participants of the Amtsilati Darussalam Assistance Board of Darussalam Boarding School Blokagung, Banyuwangi.